COMPARATIVE STUDY OF THE CHEMICAL PROPERTIES OF TRADITIONAL MEAT SHREDDED - Nuraini, Fitria Indah (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
This research purpose to analyze the chemical quality of shredded beef in the city of Malang with several types of shredded in different production codes and based on the shelf life. The material used several types of shredded with different production codes and repeated based on the shelf life. The method used an observative completely randomized design (CRD) with 12 treatments and 3 replications. The data obtained were analyzed used analysis of variance (ANOVA), if there were significant differences, it was continued with Duncan's Multiple Range Test (DMRT). The parameters are moisture content, fat content, thiobarbituric acid, water activity and oil absorption The result of this research is various types of shredded from several brands has very significant differences (p<0.01) in all of parameters.The highest moisture content, fat content, thiobarbituric acid, water activity and oil absorption is 6.373% , 30.483% , 1.787 Mg MA/kg, 0.504, 77.967% while the lowest moisture content, fat content, thiobarbituric acid, water activity and oil absorption 8%, 15.349%, 0,877 Mg MA/kg, 0.494, 23.733%.The conclusion of this study is that most of the various types of traditional processed beef shredded have good quality based on Indonesian National Standard in terms of chemical properties and physical characteristics.